Women U17 European Handball Championship in Slovakia: qualitive trend analysis - Hianik, J. (Acta Kinesiologica, 2008)
The paper is dealing with qualitative trend analysis on women U17 European handball championship in Slovakia. In the teams qualitative analysis we concentrated to the performance of 6 teams (FRA, ESP, NED, RUS, SRB, DEN). From our point of view, within the possibilities to choose the team players, implementation of the defensive and attacking playing systems of these teams were the most progressive in this age category. Each team out of the "Top 6 teams" had at least one excellent back player who was great in shooting from longer distances. Based at high shooting effectiveness from the back player area, also shooting effectiveness in the gradual attack was rather high (55%). Only Serbia and Russia used smaller number of combinations and used more individual improvisational skills of the players. Netherlands, Norway and Denmark used the system of the "quick centre", the rest of the teams used this startling type of the attack sporadically. Each of the teams of the "Top 6 ECh" disposed with 2-3 defensive systems, most frequently 6:0 and 5:1. Behavior of the players in defense was very correct, players belonging to the Top 6 teams of this tournament were technically on a high level quality (the average number of exclusions in the "ECh Top 6" teams was 4). Each team possessed one specialist player - defender, usually it was the middle defender. The most apparent difference in the effectiveness of the goalkeepers of the "ECh Top 6" and other teams was in catching effectiveness from the area of back player (51%).